Sintesis Biodiesel dari Limbah Biji Alpukat melalui Proses Esterifikasi dan Transesterifikasi - Budiastuti, Herawati; Rahmawati, Aisyah Auliya; Susanto, Susy Mardiana; Trirahayu, Dhyna Analyes; Rusdianasari, Rusdianasari (Fluida, 2023)
The avocado seed is a food waste that contains vegetable oil. The amount of avocado seed waste is very abundant, but there is no optimal processing or utilization. Fossil fuels as an energy source can experience scarcity because these energy sources are non-renewable. This research has important implications in waste management and development of renewable energy sources. One type of renewable energy is biodiesel. Biodiesel is an environmentally friendly alternative fuel made from vegetable oil. The use of biodiesel as an alternative fuel has advantages including being easier to decompose in nature and reducing emissions when compared to diesel oil. One type of plant that can be used as raw material for making biodiesel is avocado. This study aims to utilize avocado seed waste as a raw material for biodiesel synthesis and to test its characteristics that have not been found in previous studies in the form of analysis of acid value, density, and oxidation stability. The method used in the synthesis of biodiesel was esterification and transesterification reactions using methanol solvent with a mole ratio of avocado seeds to methanol of 1:6 and the addition of H2SO4 catalyst as much as 0.5% of the weight of oil for the esterification process and the addition of NaOH catalyst as much as 1% of the weight of oil for the transesterification process. This study complements previous research on biodiesel from avocado seeds and compares the obtained biodiesel characteristics to the Indonesian National Standard (SNI) 04-7182:2015. The final results of this study were 34,61%, 0.98 mg-KOH/g, 977 kg/m3, and 318 minutes for biodiesel yield, acid value, density, and oxidation stability, respectively.